Assessment of the Level of Financial and Economic Security in Organizations of the Chemical Industry: Issues of Choosing Optimal Indicators - Evgenij IVANOV; Artur SEMENOV; Anatoly SEMENOV; Maria TOLSTOVA (Communications of International Proceedings, 2021)
The article examines the external and internal conditions in which the organizations of the chemical industry carry out their activities. A conclusion is made about the need to analyze and assess regional conditions, the results of the conducted factor analysis are presented, and a risk-oriented approach to the management of the activities of chemical industry organizations is disclosed.
Keywords: Chemical industry organizations; economic security; financial security; threats to the external and internal environment.